Seed source trials of Eucalyptus grandis in Argentina - Marco, M. A. (Forest Systems, 1991)
E. grandis trees from seed sources from Australia, South Africa, Zimbabwe and Argentina were planted at two locations in the Mesopotamia Argentina. At age 5.5 years, significant differences in growth were detected among seed sources. Considering growth rate, origins from southeastern Queensland and New South Wales, in Australia and improved seed from South Africa, were considered good choices for planting in subtropical areas of the Mesopotamia Argentina.